Co–Fe Prussian Blue Analogue Intercalated into Diamagnetic Mg–Al Layered Double Hydroxides - Cuijuan Zhang (Nanomaterials and Nanotechnology, 2016)
A heterostructure of diamagnetic magnesium‒aluminium layered double hydroxides (Mg‒Al LDHs) and photomag‐ netic cobalt‒iron Prussian Blue analogue (Co‒Fe PBA) was designed, synthesized and then designated as LDH‒PB. The cyanide-bridged Co‒Fe PBA was two-dimensionally intercalated into the Mg‒Al LDH template by the stepwise anion exchange method. LDH‒PB showed ferrimagnetic properties with in-plane antiferromagnetic exchange interactions, as well as small photo-induced magnetization by visible light illumination due to the low dimensional structures and the characteristic photo-induced electronic states of the mixed valence of FeIII(low spin, S = 1/2)‒CN‒ CoII(high spin, S = 3/2)‒NC‒FeII (low spin, S = 0).